Efficacy of Fungal Laccase to Facilitate Biodethatching in Bermudagrass and Zoysiagrass. (1st July 2013) - Sidhu, Sudeep S.; Huang, Qingguo; Carrow, Robert N.; Raymer, Paul L.
Abstract : Accumulation of excessive organic matter in form of a thatch and/or mat layer can cause several problems in turfgrass management systems. A previous greenhouse study on creeping bentgrass ( Agrostis stolonifera L.) demonstrated that direct application of laccase solution every 2 wk reduced the rate of accumulation of organic matter and hence buildup of the thatch layer. A 2‐yr field study was conducted on an ultra‐dwarf bermudagrass [ Cynodon dactylon (L.) Pers. X C. transvaalensis Burtt Davy, 'TifEagle'] research green, and zoysiagrass ( Zoysia japonica Steud., 'Meyer') maintained as a home lawn to observe the influence of laccase enzyme applications on thatch development. Laccase solution was applied biweekly at the activity levels of 0 (control) and 2.1 units cm –2 . Response to laccase enzyme applications by both the turfgrass species was recorded by measuring thatch layer physical and chemical properties after 6 mo of treatment applications within each year. A significant 18 to 22% and 21 to 30% reduction in thatch layer thickness was observed for bermudagrass and zoysiagrass, respectively. Organic matter content (0–2.5 cm) decreased by 23 to 24% while saturated hydraulic conductivity increased by 19 to 30% for bermudagrass in both years. Acid‐soluble and ‐insoluble lignin was reduced in both turfgrass species after laccase treatments. Results indicate that bi‐weekly application of laccase on bermudagrass and zoysiagrass has positive impact on thatch management.